Lageplan zur Eröffnung des Mbari Artists and Writers Club 1961 - Beier, Ulli (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 1961)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Art; Painting; Africa; Exhibitions; Artists; Art Exhibition; The Mbari Club; Ibadan; Nigeria; Cultural Centre; Site Plan; Performing Arts Center; Art Collector; Art Collecting